A Vision of Blindness: Blade Runner and Moral Redemption. Issue 3 (October 2017) - Macarthur, David
Abstract : Despite its oft-noted ambiguities, critical reception of Ridley Scott's Blade Runner (Theatrical Cuts (1982); Director's Cut (1992); Final Cut (2007)) has tended to converge upon seeing it as a futuristic sci-fi film noir whose central concern is what it means to be human, a question that is fraught given the increasingly human-like replicants designed and manufactured by the Tyrell Corporation for human use on off-world colonies. Within the terms of this way of seeing things a great deal of discussion has been devoted to putative criteria of being human and the question whether the once-retired blade runner, Rick Deckard, is or is not a replicant. I aim to explore a radically different course of interpretation, which sees the film in fundamentally moral and religious terms. Put in the starkest light, the film is not about what makes us human but whether we can be saved from ourselves, from our terrifying inhumanity, our moral blindness.